2014
DOI: 10.1007/s11010-014-2274-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients with multiple sclerosis show increased oxidative stress markers and somatic telomere length shortening

Abstract: Lipid peroxidation due to oxidative stress (OS) may play an important role in the pathogenesis of chronic systemic inflammatory diseases such as multiple sclerosis (MS). Telomeres, repeated sequences that cap chromosome ends, undergo shortening with each cycle of cell division, resulting in cellular senescence. Research regarding telomere shortening has provided novel insight into the pathogenesis of various diseases. We hypothesized that OS damage leads to inflammatory reactions, which subsequently shortens t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 26 publications
3
67
2
Order By: Relevance
“…The levels of thiobarbituric acid reactive substances and advanced glycation end-products can be assessed in saliva [73]. Urine may be a good material for the assessment of urinary 8-iso-PGF2 α , which is a marker of lipid peroxidation in vivo [81]. …”
Section: The Importance Of Os In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of thiobarbituric acid reactive substances and advanced glycation end-products can be assessed in saliva [73]. Urine may be a good material for the assessment of urinary 8-iso-PGF2 α , which is a marker of lipid peroxidation in vivo [81]. …”
Section: The Importance Of Os In Msmentioning
confidence: 99%
“…Guan et al showed high levels of urinary 8-iso-PGF2 α (a marker of lipid peroxidation in vivo) in MS patients. The concentration of urinary 8-iso-PGF2 α was significantly higher in patients with SPMS and PPMS as compared to the control group [81]. It was also shown that a reduced level of prolyl oligopeptidase activity and activated α -2-macroglobulin level in the plasma were characteristic of PPMS and RRMS [51].…”
Section: The Importance Of Os In Msmentioning
confidence: 99%
“…Oxidative damage also appears to reflect in blood, saliva and urine (Karlík et al 2015;Guan et al 2015) and cerebrospinal fluid (CSF) of MS patients when compared with healthy controls (Mattsson et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress-mediated DNA damage is an important determinant of telomere shortening (e.g., Guan et al 2014;Nettle et al 2015). At critically shortened thresholds, genomic instability, replicative senescence, and apoptosis occur (Sampson et al 2006), with resultant chronic disorders (Friedrich et al 2000).…”
Section: Exercise Amelioration Of Telomeric-shorteningmentioning
confidence: 99%